2010
DOI: 10.5097/1300-0705.ucd.609-10.01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between karydakis flap repair and limberg flap for surgical treatment of sacrococcygeal pilonidal sinus (short term results)

Abstract: Amaç: Pilonidal sinus intergluteal bölgede, özellikle genç erkeklerde daha sik görülen, akut agrili veya kronik §ekli olan bir hastaliktir. Bu hastaligin tedavisinde çok sayida cerrahi teknik ve tibbi yöntem tanimlanmi §tir. Bu çaliçmada klinigimizde iki farkli cerrahi tedavi yöntemi uygulanan pilonidal sinüslü hastalann takip sonuçlanni sunmayi amaçladik. Hastalar ve Yöntem: Pilonidal sinus tedavisinde hastalara Karydakis flep (Grup 1, n=68) ve rhomboid eksizyon + Limberg flep (Grup 2. n = 74) cerrahisi uygul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Can et al 15 reported a recurrence rate of 4.6% and a complication rate of 8.9%, and Sakr et al 16 determined recurrence rates of 2.4% and a complication rate of 10% in their KF series. In a similar study, Sözen et al 17 reported a recurrence rate of 1.5% and a complication rate of 6%. In our series, no recurrence was observed in either group.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Can et al 15 reported a recurrence rate of 4.6% and a complication rate of 8.9%, and Sakr et al 16 determined recurrence rates of 2.4% and a complication rate of 10% in their KF series. In a similar study, Sözen et al 17 reported a recurrence rate of 1.5% and a complication rate of 6%. In our series, no recurrence was observed in either group.…”
Section: Discussionmentioning
confidence: 75%
“…Wound infection, fluid collection, edema, hematoma and wound separation can occur after use of the Karydakis flap procedure and other surgical techniques. The use of drains after surgery can be used to prevent fluid accumulation, edema and hematoma formation in such cases 14,17 . Gurer et al 14 reported that fluid accumulation is reduced after the routine use of post-operative drains.…”
Section: Discussionmentioning
confidence: 99%
“…Data on recurrence and follow-up times pertaining to 12,384 patients treated for PSD by Limberg and Dufourmentel flaps were extracted from 139 additional non-RCTs 4 , 60 , 103 , 104 , 115 , 126 – 128 , 133 , 156 , 157 , 196 , 199 , 201 , 208 , 221 , 224 , 242 , 261 , 262 , 267 , 289 , 302 , 303 , 313 , 318 , 321 , 322 , 334 – 336 , 348 , 372 , 399 , 407 , 410 , 415 , 417 , 426 , 433 , 438 , 439 , 444 541 . Among these patients, a recurrence of 0.4% (95% CI 0.3–0.5%) was observed in patients at 12 months, 1.6% (95% CI 1.3–1.9%) at 24 months, 5.2% (95% CI 4.5–5.8%) at 60 months, and 11.4% (95% CI 9.2–13.7%) at 120 months (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Can et al [19] and Sakr et al [20] reported complication rates of 8.9 and 10 %, respectively, in their Karydakis’ flap series. In a similar study, Sözen et al [21] reported a complication rate of 6 % and Bali et al [11] reported complications to be 10 %. Thus, complication rates of the Karydakis’ flap procedure in the hands of residents are much higher (36 %) compared to that performed by experienced surgeons (6–10 %).…”
Section: Discussionmentioning
confidence: 88%